2013
DOI: 10.1038/cdd.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Disease-relevant proteostasis regulation of cystic fibrosis transmembrane conductance regulator

Abstract: Mismanaged protein trafficking by the proteostasis network contributes to several conformational diseases, including cystic fibrosis, the most frequent lethal inherited disease in Caucasians. Proteostasis regulators, as cystamine, enable the beneficial action of cystic fibrosis transmembrane conductance regulator (CFTR) potentiators in DF508-CFTR airways beyond drug washout. Here we tested the hypothesis that functional CFTR protein can sustain its own plasma membrane (PM) stability. Depletion or inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 63 publications
(114 reference statements)
1
83
0
Order By: Relevance
“…This indicates that prior re-establishment of autophagy prolongs the persistence at the epithelial surface of a sufficient amount of functional F508del-CFTR to interrupt, for a while, the negative loop that compromises its PM residence and function. 31 We have reported that a CFTR-sufficient environment is required to allow F508del-CFTR to traffic to and reside at the PM of bronchial epithelial cells. 31 Accordingly, when F508del-CFTR is transfected into cells, the resulting protein is not expressed in the PM of CFTR-deficient HeLa cells, yet is capable of trafficking to and residing at the PM of CFTRsufficient normal bronchial epithelial cells, unless these latter cells are treated with .…”
Section: F508delmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that prior re-establishment of autophagy prolongs the persistence at the epithelial surface of a sufficient amount of functional F508del-CFTR to interrupt, for a while, the negative loop that compromises its PM residence and function. 31 We have reported that a CFTR-sufficient environment is required to allow F508del-CFTR to traffic to and reside at the PM of bronchial epithelial cells. 31 Accordingly, when F508del-CFTR is transfected into cells, the resulting protein is not expressed in the PM of CFTR-deficient HeLa cells, yet is capable of trafficking to and residing at the PM of CFTRsufficient normal bronchial epithelial cells, unless these latter cells are treated with .…”
Section: F508delmentioning
confidence: 99%
“…31 We have reported that a CFTR-sufficient environment is required to allow F508del-CFTR to traffic to and reside at the PM of bronchial epithelial cells. 31 Accordingly, when F508del-CFTR is transfected into cells, the resulting protein is not expressed in the PM of CFTR-deficient HeLa cells, yet is capable of trafficking to and residing at the PM of CFTRsufficient normal bronchial epithelial cells, unless these latter cells are treated with . 31 Indeed, the functional inhibition of CFTR in normal bronchial epithelial cells ignites the removal of endogenous wild-type CFTR from the PM by diverting CFTR recycling to lysosomal degradation.…”
Section: F508delmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfosuccinimidyl-6-(biotinamido) hexanoate (sulfo-NHS-LC-Biotin, Pierce, Rockford, IL, USA, 21335), was dissolved at 1 mg/ml in PBS (Gibco/Thermo Scientific Milan, Italy, 18912-014, pH 8.2), as described. 22 After homogenization with a Potter-Elvehjem pestle, the cells were centrifuged at 2300 × g for 15 min at 4°C. Supernatant fractions that contain the cytoplasmic and PM fractions were centrifuged 1 h at 16 000 × g at 4°C; the pellet that contains the intact membrane, was solubilized in Buffer A (20 mM Tris-HCl, pH 7.4, 2 mM EDTA, 20 mM 2-mercaptoethanol, 1 × PMSF, 1 μg/ml inhibitor protease cocktail (Sigma Aldrich, P8340)+1% Triton X-100 (Sigma Aldrich, X-100-RS) and centrifuged 1 h at 60 000 × g in the ultracentrifuge.…”
Section: Methodsmentioning
confidence: 99%
“…Nasal brushing. Freshly isolated brushed nasal epithelial cells were obtained by nasal brushing, as previously described, 20,22 from enrolled CF patients and from five non-CF consenting healthy volunteers. Brushes with cells were rapidly transferred in 15-ml sterilized tubes containing RPMI1640 medium (Invitrogen, Carlsbad, CA, USA) with 1% penicillin-streptomycin (Lonza Group LTD, Basel, Switzerland, 17-602E).…”
Section: Human Studiesmentioning
confidence: 99%